2001
DOI: 10.1097/00005537-200106000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Results of the Bone‐Anchored Hearing Aid in Unilateral Hearing Loss

Abstract: The use of BAHA has significantly improved the hearing handicap scores in patients with unilateral conductive or mixed hearing loss. The proven safety and efficacy of the device promote its use in unilateral cases that traditionally had been left unaided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0
5

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(68 citation statements)
references
References 5 publications
(3 reference statements)
3
60
0
5
Order By: Relevance
“…There are various reports of BAHA fittings on adults with profound UHL. [54][55][56][57] These results ranged from no improvement in localization to improvement of speech in noise, improved performance compared with other device fittings, and subjective reports of benefit.…”
Section: Nonconventional Hearing Technologymentioning
confidence: 98%
See 1 more Smart Citation
“…There are various reports of BAHA fittings on adults with profound UHL. [54][55][56][57] These results ranged from no improvement in localization to improvement of speech in noise, improved performance compared with other device fittings, and subjective reports of benefit.…”
Section: Nonconventional Hearing Technologymentioning
confidence: 98%
“…In addition, benefit is often smaller or not present in conditions where the speech and noise come from the same direction or the speech is in front and the noise surrounds the listener. 55,61 Although the BAHA is available for children with severe-to-profound UHL, no studies to date have been reported on BAHA fittings with children with severe to profound hearing loss.…”
Section: Nonconventional Hearing Technologymentioning
confidence: 99%
“…Koristi se kod trajne konduktivne ili mešovite nagluvosti lakog i srednje teškog stepena, kod kojih drugim operacijama nije moguće popraviti sluh. Može se primeniti i kod jednostrane gluvoće, ukoliko je sluh na drugom uvu očuvan (Wazen, 2001(Wazen, , 2003Snik, 2002;Niparko, 2003).…”
Section: Uvodunclassified
“…Although its mechanism of transmitting/receiving sides, where wireless signals are transmitted from the approaching motor-car periodically and the safety equipment of worker informs the worker of the alarm on approaching motor-car after receiving them, is the same as that explained in the previous section, but it is different in that the form of safety equipment for worker is the safety helmet using the bone conduction speaker [16][17][18]. That is, it shows the possibility of utilization in various other forms of safety equipment proposed by the authors by applying the form of safety equipment for worker only to the safety helmet to be worn by the maintenance worker while using the configuration of transmitting/receiving sides developed already in the previous section.…”
Section: Utilization Of the Developed Safety Equipment In The Other Formmentioning
confidence: 99%